2008
DOI: 10.1113/jphysiol.2008.161430
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐dependent contractions: when a good guy turns bad!

Abstract: Endothelial cells can induce contractions of the underlying vascular smooth muscle by generating vasoconstrictor prostanoids (endothelium-dependent contracting factor; EDCF). The endothelial COX-1 isoform of cyclooxygenase appears to play the dominant role in the phenomenon. Its activation requires an increase in intracellular Ca 2+ concentration. The production of EDCF is inhibited acutely and chronically by nitric oxide (NO), and possibly by endothelium-dependent hyperpolarizing factor (EDHF). The main prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
159
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(170 citation statements)
references
References 107 publications
(179 reference statements)
8
159
1
2
Order By: Relevance
“…In contrast to this, COX-1 is the main regulated enzyme in the rat aorta, 19 in which many studies on the identity of EDCF were performed. 1 Thus, the prostanoid synthetic pathways in humans appear to be closer to the hamster than the rat, as also suggested by the authors.…”
supporting
confidence: 68%
See 3 more Smart Citations
“…In contrast to this, COX-1 is the main regulated enzyme in the rat aorta, 19 in which many studies on the identity of EDCF were performed. 1 Thus, the prostanoid synthetic pathways in humans appear to be closer to the hamster than the rat, as also suggested by the authors.…”
supporting
confidence: 68%
“…In a recent review by the same group, the contribution of PGF 2␣ to endothelium-dependent contraction has been considered marginal. 1 On the other hand, there might be situations, such as senescence, in which metabolic enzymes may become insufficient to degrade efficiently released PGs in conditions of elevated biosynthesis, including PGH 2 , thromboxane A 2 , and PGF 2␣ . 21 Because of the rapid hydrolysis of thromboxane A 2 into the inactive thromboxane B 2 and the (spontaneous) conversion of PGH 2 into PGF 2␣ , PGF 2␣ may locally accumulate and cause vasoconstriction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that an increase in the release of EDCF can lead to abnormal function of the endothelium and that occurs in different various vascular disorders. A variety of stimuli can cause EDCF production, including agonists like acetylcholine, adenosine nucleotides or by stretch 25. Inflow of calcium ions into the cells of the endothelium would occur in response to the different triggering elements.…”
Section: Discussionmentioning
confidence: 99%